Is there mush-room to improve the environmental sustainability of psilocybin production? - Luke Lanham; Alistair McTaggart; James R. Falconer (Journal of CO2 Utilization)
Mental health disorders and associated economic impact continue to rise domestically and globally. In 2023, to expand treatment options for individuals suffering Treatment Resistant Depression (TRD), the Therapeutic Goods Administration (TGA) of Australia has permitted psychiatrist lead psilocybin-assisted psychotherapy. Psilocybin, a psychedelic tryptamine found naturally in psychedelic mushrooms is presently synthesised, for clinical use, through synthetic or chemoenzymatic methods. Unfortunately, the synthesis-based methods are limited by low production yields, high material costs, multiple steps, and laborious in-process controls. Use of neoteric (“new”) solvents, such as supercritical carbon dioxide (scCO2) offers an environmentally sustainable alternative to synthetic techniques. Favoured for its selective extraction, low supercritical process parameters (31.7°C and 72 bar), high permeability through plant matrices, and a lack of post-extraction residues, supercritical carbon dioxide (scCO2) presents a promising option for extracting novel psychedelic tryptamines from the fungi biomass. Presently, no publications demonstrate the use of scCO2 in the extraction of psychedelic tryptamines from any plant biomass. Herein, to better understand the plausibility and need of alternative psilocybin supply pathways, the current synthetic, biosynthetic and chemoenzymatic production options are reviewed and compared to the possibility of scCO2 extraction from the fungi biomass as a viable, environmentally conscious alternative. Additionally, a brief overview of psychedelic mushrooms and the medicinal importance of their psychedelic tryptamines is provided.